Biographical Work in Queer Volunteering. Findings from a Case Study on German Young Adults - Leinhos, Patrick (SocietàMutamentoPolitica, 2025)
While research has revealed subjective, biographical and identity-related meanings of volunteering, gendered perspectives have not yet been given a central focus. Little is known about the impact that volunteering has on construction of (gendered) biographies. The present study aims to address this research gap by undertaking a biography-analytical study of young adults involved in queer volunteering, exploring the influence of queer volunteering on the (gendered) construction of their biography. By using the documentary method of interpretation, relations between queer volunteering and the biographies of the volunteers were reconstructed. In this article, the central ways in which the biographies of queer activists are presented in their biographical interviews are firstly presented and reflected upon. All the cases in the underlying sample use theorising and argumentative modes to construct their biographical self-representations. Then, the manner in which young adults engage in biographical work is reconstructed. To conclude these aspects, queer volunteering contexts are discussed as spaces for biographical work. In queer volunteering contexts, volunteers are able to identify themselves, develop the necessary competences to deal with everyday challenges, regain their agency, find visible role models and thus opportunities and anchors for biographisation.